TYPES AND SCALE OF POLITENESS MAXIMS IN LITTLE WOMEN MOVIE - Farha Fahira; Tri Wahyu Retno Ningsih (Universitas Gunadarma, 2022)
The aims of this research were to find out types and scales of politeness maxims that used in the subtitle of Little Women movie. This research used descriptive qualitative method with steps to explain context of situation when the conversation happened then interpret each of data relate to politeness maxim types and explain the scales of politeness that used in the subtitle of the movie. The results showed that there were six types of politeness maxims in the subtitle of Little Women movie, they were 10 generosity maxims, 8 tact maxims, 10 approbation maxims, 3 modesty maxims, 5 sympathy maxims, and 14 agreement maxims. The most frequently maxim that used in the subtitle of Little Women movie was agreement maxim. Agreement maxim became the most frequently maxim that used in the subtitle of Little Women movie was because the characters frequently focused on agreeing someone ideas or avoiding disagreement someone ideas. The results also showed that there were some scales of politeness maxims in the subtitle of Little Women movie, they were 10 cost-benefit scales, 3 optionality scales, 4 authority scales and 33 social distance scales. The most frequency scale that used in the subtitle of Little Women movie was social distance scale. Social distance scale became the most frequently scale that used in the subtitle of Little Women movie was because the most characters in that movie was a family, then the participants knew well or familiarity of each other.